(untitled) (Experimental biology, 2017)
The short characteristic of the basic versions of bacterial test systems on mutation and a reparation, applied in ecotoxicology is resulted. Their merits and demerits are discussed. Is developed new updating Rec-hromotests. It is recommended for use in genetic toxicology at screenings researches for definition of DNA-trops and antigen toxics to activity of various factors.